The Effectiveness of Empathy Training on Social Adjustment and School Belonging in Elementary Sixth-Grade Students - Maryam Safara; Somaye Rafiee (Iranian Evolutionary Educational Psychology Journal, 2020)
The present study aimed to investigate the effectiveness of empathy training on social adjustment and belonging to the school in elementary school students. The present study was conducted as a semi-experimental two-group pretest-posttest design. The statistical population was all sixth grade elementary school students in Tabas city in the academic year of 2016-2017. The study sample was 30 people who were selected by cluster random sampling method. The tools used to collecting data were: Belonging to school inventory and  Bell’s adjustment inventory  For data analysis, Descriptive statistics such as mean, standard deviation, and Univariate and Multivariate analysis of covariance were used (p < 0.01). The findings indicated that the mean of the experimental group in the components of social adjustment and belonging to the school increased compared to the control group (p <0.05). Therefore, it can be concluded that empathy training has been effective in increasing social adjustment and students’ belonging to the school.